Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Merger dan Akuisisi Pada Perusahaan Non Keuangan Yang Terdaftar di BEI Periode 2017-2021 - Noval, Khamada; Putra, I Nyoman Nugraha Ardana; Husnan, Lalu Hamdani; Hidayati, Siti Aisyah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This study aims to analyze the comparison of financial performance before and after mergers and acquisitions in non-financial companies listed on the IDX in the period of 2017-2021. This research is a comparative research with quantitative data. The data used is in the form of financial statements of non-financial companies 1 year before and 1 year after mergers and acquisitions. Samples were taken using purposive sampling technique. In this study, the sample amounted to 33 companies out of 73 companies, therefor the research data analyzed in this study amounted to 66 observations. The data analysis method used is descriptive test, normality test, and hypothesis testing using the non-parametric wilcoxon signed rank test. The results of this study indicate that the liquidity ratio has decreased but not significantly which indicates that there is no significant difference before and after mergers and acquisitions. While the profitability, leverage, and activity ratios experienced an increase but were not significant which showed no significant difference before and after the merger and acquisition